2010
DOI: 10.3997/1873-0604.2010054
|View full text |Cite
|
Sign up to set email alerts
|

Full‐waveform inversion of cross‐hole ground‐penetrating radar data to characterize a gravel aquifer close to the Thur River, Switzerland

Abstract: Cross‐hole radar tomography is a useful tool for mapping shallow subsurface electrical properties viz. dielectric permittivity and electrical conductivity. Common practice is to invert cross‐hole radar data with ray‐based tomographic algorithms using first arrival traveltimes and first cycle amplitudes. However, the resolution of conventional standard ray‐based inversion schemes for cross‐hole ground‐penetrating radar (GPR) is limited because only a fraction of the information contained in the radar data is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…The adjoint-based method has been successfully tested on field data (Ernst et al, 2007a;Klotzsche et al, 2010). In addition the suggested probabilistic inversion strategy needs substantially more (computationally expensive) forward calculations than does the traditional adjoint-based approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjoint-based method has been successfully tested on field data (Ernst et al, 2007a;Klotzsche et al, 2010). In addition the suggested probabilistic inversion strategy needs substantially more (computationally expensive) forward calculations than does the traditional adjoint-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the algorithm of Ernst et al (2007b) has been improved such that it exploits the full vector field of the electromagnetic wave propagation and allows for arbitrary antennae geometry . Klotzsche et al (2010) demonstrate an application of the improved code to crosshole GPR waveform data acquired in a gravel aquifer. Lately, Meles et al (2011) demonstrated that the adjoint-based method of Ernst et al (2007b) becomes less sensitive to the starting model when the inversion is conditioned to the long wavelengths of the signal in the initial part of the inversion and higher frequencies are gradually incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…Both procedures are dependent on the electrical permittivity and conductivity starting models and must therefore be re-done when these are altered. A comprehensive description of how to apply the FWI approach to field data can be found in Klotzsche et al (2010) and Keskinen et al (2017).…”
Section: Gpr Post-processing and Inversionmentioning
confidence: 99%
“…The recorded EM signal provides information on the electrical permittivity and the electrical conductivity of the investigated formation, that can be related to velocity and the attenuation of the EM wave, respectively (Annan, 2005). To date, published field studies using crosshole GPR only include sediments with low electrical conductivity, e.g., unconsolidated sands (Cassiani et al, 2006;Irving et al, 2007;Haarder et al, 2015;Looms et al, 2008;Klotzsche et al, 2010;Gueting et al, 2015), sandstone (Binley et al, 2002), and chalk (Keskinen et al, 2017). In general, clayey environments have been avoided as the attenuation of the EM signal reduces the signal strength and thereby the possible distance between boreholes.…”
Section: Introductionmentioning
confidence: 99%
“…This approach much better extracts the information of the measured GPR data and can much more accurately simulate EM wave propagation, boundary conditions and antenna properties. This approach was first used in seismic inversion [24,25], then introduced to crosshole GPR inversion [26,27], and is an enormous improvement over ray-based inversion [5,6,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%